Historical Rights of States to Maritime Water Areas and the Legal Status of the Sea of Okhotsk - V. V. Gavrilov; R. M. Nurimbetov (Московский журнал международного права, 2023)
INTRODUCTION. Based on the study of the international law, doctrine and practice of states, the article analyzes the content of the institution of the historical rights of the state to the sea areas, its correlation with the provisions of the 1982 UN Convention on the Law of the Sea, as well as the legal status of the Sea of Okhotsk and the possibility of its adjustment in in the context of a possible statement by Russia that it has historical rights to its water area.  MATERIALS AND METHODS. The issues raised in the article are structurally divided into three main groups. The first one is related to the study of the reasons for the emergence of the institution of historical rights of states to maritime areas in the international law of the sea, as well as its correlation with the legal mechanisms for the delimitation and use of maritime spaces defined by the 1982 UN Convention. The second is devoted to studying the structure of this institution and definition of the concept and content within its framework of such key notions and categories as “historical bays”, “historical waters”, “historical legal foundations”, “historical title of the state” and some others. The third group is directly connected with the definition of the fundamental possibility and potential scope of the extension of the Russian Federation historical rights to the waters of the Sea of Okhotsk.  RESEARCH RESULTS. When writing the work, the authors proceeded from the fact that despite the limited potential of Russia's possible actions to defend its historical title to the Sea of Okhotsk, they can not be considered unpromising in the foreseeable historical perspective. At the same time it should be borne in mind that the way to achieve success in solving this problem should not lie in declaring its water area an inland sea or historical waters of Russia, but in legitimizing by our state a number of its exclusive historical rights in this maritime area based on Russia's vital interests.  DISCUSSION AND CONCLUSIONS. The content of the institution of the historical rights of states to maritime spaces, as well as the new political reality, give the Government and the State Duma of the Russian Federation all the necessary grounds for raising the question of a partial change in Russia's position on the legal status of the Sea of Okhotsk and the development of a new strategy for upholding Russia's historical rights to its water area, as through the adoption of unilateral internal legal acts, and through the implementation of a consistent policy to disseminate and uphold this point of view in international relations within the framework of negotiations with foreign states and the activities of relevant international bodies and organizations.